Creating patients: how technology and measurement approaches are misused in diagnosis and convert healthy individuals into TMD patients - Greene, Charles; Manfredini, Daniele; Ohrbach, Richard (Frontiers in Dental Medicine, 2023)
The advances made in recent years regarding technological approaches to medical and dental diagnosis are impressive. However, while those tools, procedures, and instruments may produce an improved clinical diagnosis or discover a new disorder, they also can be misused and misinterpreted in various ways. In the field of temporomandibular disorders (TMDs), the very nature of those conditions is similar to common orthopedic problems elsewhere in the body. Yet, beyond imaging of the affected areas, there have been few important new technological approaches to augment the traditional history and examination for a sufficient diagnosis of such problems. The traditional approach is exemplified by the Diagnostic Criteria for Temporomandibular Disorders, which has high inter-examiner reliability and diagnostic validity; translations into over 20 languages allow for widespread use. In contrast and unfortunately, the TMD field is replete with a variety of so-called diagnostic instruments and procedures, which have not been tested for diagnostic validity; these instruments and procedures, through misuse, are capable of complicating a true diagnosis of patients who present with symptoms, while also creating new patients by finding so-called abnormalities in healthy subjects. This paper discusses those technological approaches and their misuse with respect to TMD diagnosis from a critical viewpoint, and the authors argue that there are significant risks for patients if their uncritical implementation becomes accepted and widespread. Therefore, dentists are encouraged to reject the proposed application of such technological approaches to diagnosis of the stomatognathic system.